Efektivitas Guided Imagery Terhadap Penurunan Tekanan Darah Pada Hipertensi - Herliana, Irma; Solehudin, Solehudin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The phenomenon of hypertension in society is a serious and quite common health problem. Unhealthy lifestyles, such as a diet high in salt, lack of physical activity, excessive alcohol consumption, and smoking, can increase the risk of hypertension. The aim of this community service activity is to increase public knowledge in managing blood pressure using Guided Imagery therapy. Community Service Activities in the form of Health Education with the theme